Seasonal Variation of Megabenthos Abundance and Spatial Distribution in the GITA NADA Marine Protected Area, Sekotong, West Lombok - Raja Aditya Sahala Siagian; Relis Gabriel Sihaloho; Muhammad Farhan Anshory; M. Gilang Aktia; Ruhul Anshori; Kara M A Majerus (Jurnal Biologi Tropis, 2026)
Megabenthos are organisms that inhabit the benthic zone and live on or within the substrate, including biota that attach, crawl, or burrow, and which function as important components of benthic food webs. This study aimed to determine the distribution patterns abundance and frequency of occurrence megabenthos during the dry and wet seasons in the GITA NADA Marine Protected Area (MPA), West Lombok. Megabenthos data were collected using the belt transect method. Results showed that megabenthos abundance at all locations within the GITA NADA MPA at depths of 3–5 m was 16,59 ind/m² in the dry season and 13,83 ind/m² in the wet season, while at depths of 8–10 m abundance was 39,74 ind/m² in the dry season and 38,25 ind/m² in the wet season. Independent t-tests indicated no significant differences in megabenthos abundance between the dry and wet seasons at either depth (3–5 m and 8–10 m). Frequency of occurrence megabenthos at depths of 3–5 m ranged from very rare to moderate in both the dry and wet seasons. At depths of 8–10 m, frequency of occurrence ranged from very rare to moderate in the dry season and from very rare to absolute in the wet season. The Morisita index values for megabenthos distribution in the GITA NADA MPA ranged from −0,0005 to 0,492, indicating both uniform and clumped distribution patterns.